2012
DOI: 10.4014/jmb.1108.08047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Probiotic Strain, Enterococcus faecium, on the Immune Responses of Olive Flounder (Paralichthys olivaceus)

Abstract: The present study was aimed to investigate the effect of a probiotic, Enterococcus faecium, on the immune responses against infection with the marine fish pathogen Lactococcus garvieae in olive flounder (Paralichthys olivaceus). The immune responses were assessed by lysozyme activity, complement activity, protease activity, and expression of proinflammatory cytokines by RT-PCR. The lysozyme and complement activities were increased between 9 to 15 and 9 to 13 days, respectively, and antiprotease activity was sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…BGO supplementation was unable to incite significantly higher serum MPO and antiprotease activities in this study. Similar results were reported for MPO (Park et al., ) and antiprotease activities (Heo et al., ; Kim et al., ) in fish fed different types of probiotics. The mechanism behind the innate immunity response to BGO upon its oral administration to olive flounders remains unclear, but it may be that beneficial intestinal bacteria metabolize the BGO.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…BGO supplementation was unable to incite significantly higher serum MPO and antiprotease activities in this study. Similar results were reported for MPO (Park et al., ) and antiprotease activities (Heo et al., ; Kim et al., ) in fish fed different types of probiotics. The mechanism behind the innate immunity response to BGO upon its oral administration to olive flounders remains unclear, but it may be that beneficial intestinal bacteria metabolize the BGO.…”
Section: Discussionsupporting
confidence: 86%
“…So far information found, the in vivo study on BGO, as a potential prebiotic on terrestrial or aquatic species, has not been reported yet. In sequence of our previous successful studies on the effects of different immunostimulatotry agent and probiotics on olive flounders (Heo, Kim, Kim, Bai, & Kong, ; Hong et al., ; Kim et al., ) and concerning best response (growth and immunity) in olive flounder supplemented with 0.1% feed additives (Lee et al., ; Won, Kim, & Park, ; Yoo et al., ), in this research, we aimed to inoculate 0.1% BGO as a feed supplement in this commercially valuable cultured fish. The objective of the present study was to identify BGO's prebiotic potential in olive flounder aquaculture and elucidating its effects on the innate immunological parameters as well as prevention ability against streptococcosis.…”
Section: Introductionmentioning
confidence: 99%
“…Lysozyme activity is an important innate humoral parameter of bactericidal activity; lysozyme acts as an opsonin that activates both the complement system and phagocytes (Burge, Madigan, Burnett, & Burnett, ; Dash, Das, Samal, & Thatoi, ; Magnadottir, ). Importantly, lysozyme not only destroys the β‐(1,4)‐linked N ‐acetylglucosamine and N ‐acetylmuramic acid components of gram‐negative bacteria but also destroys other types of threatening pathogens that are phagocytosed by macrophages and neutrophils (Kim et al, ; Satyanarayana, Kumar, Naidu, & Prasad, ). In fact, phagocytes, mainly neutrophils, are believed to be the main sources of plasma lysozyme (Cecchini, Terova, Caricato, & Saroglia, ), and increases in lysozyme activity have been associated with neutrophilia (Muona & Soivio, ).…”
Section: Discussionmentioning
confidence: 99%
“…The second most investigated genus is Lactococcus (Balcázar et al, 2007b ; Kim et al, 2013 ; Beck et al, 2015 , 2016 ; Nguyen et al, 2017 ). Genera of Enterococcus, Pediococcus , and Leuconostoc have also been studied at a significant level; Enterococcus (Wang et al, 2008 ; Kim et al, 2012 ; Rodriguez-Estrada et al, 2013 ; Matsuura et al, 2017 ), Pediococcus (Neissi et al, 2013 ; Dawood et al, 2016a ; Kaew-on et al, 2016 ), Leuconostoc (Balcázar et al, 2007b ). Although the majority of the studies used a specific strain of live LAB (Table 7 ), some studies were performed with their inactivated form of LAB (Table 8 ).…”
Section: Practical Uses Of Lab As An Immunostimulant In Finfish Aquacmentioning
confidence: 99%
“…As expected, a vast majority of studies employed dietary LAB as the mode of administration. However, some studies treated the fish by intraperitoneal injection (Kim et al, 2012 ; Matsuura et al, 2017 ) or immersion in a LAB-containing bath (Wang et al, 2008 ). Many studies indicated that the feeding administration demonstrated better immunostimulant effects, compared to any other modes of application.…”
Section: Practical Uses Of Lab As An Immunostimulant In Finfish Aquacmentioning
confidence: 99%